A DFT based analysis of LiYX (X = C, Ge, Si) alloys for energy applications. (2022) - Kumar, Dinesh; Chand, Prakash; Mohan, Lalit
Highlights: Structural, Electronic, and optical properties of LiYX (X = C, Ge, Si) half-Heuslar compounds based on density functional theory (DFT) are investigated. The LiYGe and LiYSi alloys have a direct bandgap of 0.68 eV and 0.61 eV at point X, whereas the LiYC compound has an indirect bandgap of 0.48 eV with band transition X → Γ. Optical conductivity of LiYC, LiYGe, and LiYSi compounds is found to be 7322, 9071, and 8212 in the units of Ohm −1 cm −1 near the UV region. The maximum reflectivity of 0.7 for LiYC is obtained at 5 eV, 0.6 for LiYGe in the range 10–14 eV, and 0.6 for LiYSi in the energy range 9–14 eV are obtained. The maximum extinction coefficient of 3 for LiYX alloys in the energy range 3–12 eV is obtained which lies in visible and UV regions. Abstract: LiYX (X = C, Ge, Si) half-Heuslar compounds are examined using density functional theory (DFT). WIEN2K kit is used to compute Structural, electronic & optical properties. The full Potential (FP) linearized augmented plane wave (LAPW) technique is used for the calculations. The compounds have optimized lattice parameters in the range 5.7–6.6 Å. The density of states and band structure were also determined and evaluated. The LiYGe and LiYSi alloys have a direct bandgap of 0.68 eV and 0.61 eV at point X, whereas the LiYC compound has an indirect bandgap of 0.48 eV with band transition X → Γ. The optical reflectivity of the alloys is in the ultraviolet region. The high absorption coefficient (>10 4 cm −1 ) is obtained. The respective optical conductivity of LiYC, LiYGe, and LiYSi compounds is found to be 7322, 9071, and 8212 in the units of Ohm −1 cm −1 near the UV region. Using real and imaginary parts of the dielectric function, the reflective index, absorption coefficient, electron energy loss, extinction coefficient were also analyzed. Half-Heusler alloys due to their potential applications in solar energy or thermoelectrics are of great interest nowadays. Our results revealed that these compounds are more appropriate candidates for solar and photovoltaic energy applications based on energy bandgap and optical studies. These alloys may act as an alternative to the CdS buffer layer to increase the performance of the device. For experimental fabrications, our computed data may be used as a reference.